Design and evaluation of a sintered metal fiber filter for gasoline direct injection engine exhaust aftertreatment. (July 2019) - Ou, Qisheng; Maricq, M. Matti; Pakko, James; Chanko, Timothy B.; Pui, David Y.H.
Abstract: A novel metal fiber gasoline particulate filter (GPF) is designed and evaluated as a potential improvement to the traditional automotive wall flow substrate. A procedure based on single fiber efficiency theory and the Kuwabara flow model for fibrous filter media is developed to optimize filter design. The prototype design is derived from two constraints, namely to maximize PM removal efficiency while minimizing filter backpressure. Metal fibers are chosen that tolerate gasoline engine exhaust temperatures and pleating is used to fulfill size limits dictated by vehicle space constraints. Two prototypes are evaluated by vehicle and engine dynamometer testing. These tests reveal PM filtration efficiencies of greater than 78% for both the FTP and US06 drive cycles, with an average backpressure of approximately 1 kPa over a US06 drive cycle on a 2.0 L GDI light duty vehicle. Measured PM removal efficiencies at constant exhaust temperature and flowrate agree well with model predictions. Backpressure predictions agree withs measurements after accounting for GPF entrance and exit effects. The metal fiber GPF performance is discussed relative to the current state of the art wall flow filters and the limited literature data on metal foam filters. Whereas the fibrous media offers excellent efficiency and backpressure penalty, achieving surface areas comparable to wall flow substrates remains a challenge for practical implementation. Highlights: A novel sintered metal fiber gasoline particulate filter (GPF) is designed and evaluated for vehicle engine particulate matter after-treatment application. The GPF prototypes are designed using an optimization procedure based on single fiber efficiency theory. Prototypes are manufactured based on the design optimization and evaluated by vehicle and engine dynamometer testing.